Master Facility Inventory: Nursing and Residential Care Homes, 1982 ([Verlag nicht ermittelbar], 1987)
This National Master Facility Inventory data file is intended to provide a comprehensive list of nursing homes and related care homes in the United States in 1982. The criteria for inclusion were that a home maintained three or more inpatient beds and provided one or more personal care services (such as help with eating, walking, correspondence, dressing, bathing, or using the toilet) or supervisory care. The file contains the names and addresses of 26,817 such facilities along with characteristics such as total beds set up and staffed for use, number of beds certified by Medicare or Medicaid as skilled and intermediate beds, total residents, and type of ownership. Facilities that only provided services to the mentally ill or the mentally retarded are not included in this file. Each facility has a unique identification number that incorporates the Federal Information Processing Standards state and county codes for sorting and selection by state, county, city, or zip code.